Pediatric patient classification system: improvement of an instrument - Ariane Polidoro Dini; Edinêis de Brito Guirardello (SciELO, 2014)
Objective Improve the content validity of the instrument for classification of pediatric patients and evaluate its construct validity. Method A descriptive exploratory study in the measurement of the content validity index, and correlational design for construct validation through exploratory factor analysis. Results The content validity index for indicators was 0.99 and it was 0.97 for graded situations. Three domains were extracted in the construct validation, namely: patient, family and therapeutic procedures, with 74.97% of explained variance. The instrument showed evidences of content and construct validity. Conclusion The validation of the instrument occurred under the approach of family-centered care, and allowed incorporating some essential needs of childhood such as playing, interaction and affection in the content of the instrument.